Fifty-six percent of proximal femoral cortical hypertrophies 6 to 10 years after total hip arthroplasty with a short cementless curved hip stem: a cause for concern? - Innmann, Moritz Maximilian; Weishorn, Johannes; Bruckner, Thomas; Streit, Marcus R.; Walker, Tilman; Gotterbarm, Tobias; Merle, Christian; Maier, Michael Wolfgang (BMC musculoskeletal disorders, 2019)
Thigh pain and cortical hypertrophies (CH) have been reported in the short term for specific short hip stem designs. The purpose of the study was to investigate 1) the differences in clinical outcome, thigh pain and stem survival for patients with and without CHs and 2) to identify patient and surgery-related factors being associated with the development of CHs.
Gesehen am 03.07.2019